THE PROBLEMS OF IMPLEMENTING SURVEY METHODS IN RESEARCHING PROCESS (Ustozlar uchun, 2025)
This thesis provides a comprehensive examination of survey methodology and its methodological foundations, widely applied in modern scientific research. The study analyzes the essence, forms, types, and practical mechanisms of conducting surveys within a structured scientific framework. Key methodological aspects such as identifying the purpose of the survey, selecting respondent groups, developing question typologies, and ensuring anonymity and reliability are discussed in detail. In addition, the study highlights methodological approaches used in qualitative and quantitative research, criteria for assessing validity and reliability, as well as procedures for data processing, analysis, and interpretation. The findings demonstrate that survey methodology is an effective, accurate, and systematic tool for data collection in scientific investigations.